Pro Apache Ant - Moodie, Matthew (Apress, 2012)
In this first chapter, I will give you an overview of Ant so that even someone who has never come across it before will be up to speed on what Ant is, why it was created, and why it is such a useful tool. To start, I will deal with the history of complex programming projects and the evolution of build tools. By looking at the history of build tools, it should become clear why the creators of Ant produced a new build tool. Placing the Ant project in context will be a useful exercise.